6 - Climate Information for Development: An Integrated Dissemination Model - Tarhule, Aondover Augustine (Africa Development, 2007)
This paper describes a new conceptual model of climate research and seasonal forecast dissemination for West Africa. The model was developed through a survey of 600 climate information end-users and 27 organisations in four West African countries – Burkina Faso, Mali, Niger and Nigeria. Despite significant advances in climate research and climate forecasting, the majority of African countries continue to suffer the full impacts of climate variability with serious adverse implications for economic growth and development. These countries are yet to experience the benefits of climate research for mitigating impacts. The major challenge is lack of access to, and ability to respond to, climate re- search information by both vulnerable groups and institutions and agencies charged with managing the impacts of climate variability. Additionally funding agencies outside the continent drive much of the research on African climate dynamics. Indeed few African countries have the resources, technical expertise and, in some cases, political commitment to give the necessary priority to cli- mate and environmental research. Therefore, it is important to develop innova- tive strategies that allow them to take advantage of the results of climate re- search. The proposed model consists of a regional archive and database for all research related to West African climate variability. The goal is to improve ac- cess to emerging research findings and technologies and to avoid duplication of efforts. A second major component includes an institute dedicated to the testing, validation and adaptation of research for practical applications under local con- ditions. The model illustrates clearly the pathways of climate research informa- tion flow and linkages between the research community, policy makers, the media and end-users. Although based on research in West Africa, the model can easily be adapted for other parts of Africa.